2017
DOI: 10.12659/msm.908213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Total Knee Arthroplasty Performed Using Patient-Specific Cutting Guides

Abstract: BackgroundPatient-specific instruments have recently gained attention for ensuring the accuracy of osteotomy and correct alignment in total knee arthroplasty (TKA). We aimed to report our experience with TKA performed by using CT-based 3D model of cutting guides in our clinic.Material/MethodsA total of 36 patients (mean age, 67.58±8.46 years; 24 females, 12 males) who underwent TKA with 3D patient-specific cutting guides in our clinic were included in the study. Differences between preoperatively planned bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…b After the wedge was removed, the locking guide was fixed on the femur with the remaining K-wires. c After the wedge was closed accurately, the bolt was inserted patient-specific cutting guides to provide intra-operative guidance for better placement of the implant in total knee arthroplasty (TKA) and to increase the accuracy of osteotomy and post-operative alignment [20]. In the present study, 3Dprinted cutting guides and locking guides were used to locate the osteotomy cut plane and to facilitate closing the wedge respectively for MCWDFO.…”
Section: Discussionmentioning
confidence: 99%
“…b After the wedge was removed, the locking guide was fixed on the femur with the remaining K-wires. c After the wedge was closed accurately, the bolt was inserted patient-specific cutting guides to provide intra-operative guidance for better placement of the implant in total knee arthroplasty (TKA) and to increase the accuracy of osteotomy and post-operative alignment [20]. In the present study, 3Dprinted cutting guides and locking guides were used to locate the osteotomy cut plane and to facilitate closing the wedge respectively for MCWDFO.…”
Section: Discussionmentioning
confidence: 99%
“… 16 3D-PSIs have emerged as an alternative technique to conventional methods due to their ability to mold to patient-specific anatomy and have shown high accuracy and consistency in pathologies. 17 , 18 , 19 Previous systematic reviews have found that 3D-PSIs have accurate coronal plane alignment with decreased operative times and intraoperative fluoroscopy for osteotomies. 12 , 14 This technique has demonstrated good short-term outcomes postoperatively.…”
Section: Discussionmentioning
confidence: 99%